1982
DOI: 10.1056/nejm198210073071503
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Adjuvant Chemotherapy and Immunotherapy in Cutaneous Melanoma

Abstract: In a randomized trial of adjuvant chemotherapy, immunotherapy, or immunochemotherapy, 761 evaluable patients with pathological Stage II cutaneous melanoma anywhere on the body or with pathological Stage I melanoma of the trunk (Clark's level 3 to 5) were studied by the World Health Organization International Melanoma Group. Wide local excision and excisional regional lymphadenectomy alone were performed in 185 patients and the results were compared with those of surgery plus chemotherapy with dacarbazine (in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(38 citation statements)
references
References 12 publications
0
33
0
3
Order By: Relevance
“…32 Moreover, a number of randomized trials have indicated that BCG is not effective as a postsurgical adjuvant treatment of melanoma. 33 Similarly, the topical application of DNFB that we employed cannot be considered therapeutic. Neither DNFB nor the related compound, DNCB, has systemic antitumor effects; 34 furthermore, 4 of the 6 patients who exhibited partial or complete tumor regression in our study did not receive DNFB before sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, a number of randomized trials have indicated that BCG is not effective as a postsurgical adjuvant treatment of melanoma. 33 Similarly, the topical application of DNFB that we employed cannot be considered therapeutic. Neither DNFB nor the related compound, DNCB, has systemic antitumor effects; 34 furthermore, 4 of the 6 patients who exhibited partial or complete tumor regression in our study did not receive DNFB before sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Two trials compared dacarbazine versus observation [349,350], one trial compared dacarbazine to placebo [351], and one trial investigated dacarbazine in combination with BCG versus observation [352]. Only one study examined methyl-CCNU [353].…”
Section: Level Of Evidence 1amentioning
confidence: 99%
“…The early trials of adjuvant melanoma immunotherapy failed to show prolongation of patient survival (Fisher et al, 1981;Kaiser et al, 1981;Veronesi et al, 1982), but the role of the recombinant IFNs had yet to be tested. All subtypes of IFN have now been explored to prevent melanoma recurrence after disease resection.…”
Section: Does Adjuvant Interferon Offer Survival Benefit?mentioning
confidence: 99%